Epidemiological perspectives of ticks and tick-borne diseases in South Sudan: Cross-sectional survey results - Fredrick M. Kivaria (Onderstepoort Journal of Veterinary Research, 2012)
A cross-sectional study was conducted between September and October 2010 in five states of South Sudan that were selected on the basis of the perceived risk of tick-borne diseases. The purpose was to investigate epidemiological parameters of tick-borne diseases in South Sudan and their uses in future control strategies. A total of 805 calves were assessed by clinical, microscopic and serological examination and tick counts. The indirect Enzyme-Linked Immuno-Sorbent Assay (ELISA) was used to detect antibodies to Theileria parva, Theileria mutans, Anaplasma marginale and Babesian bigemina. Sero-conversion risks for T. parva and T. mutans were 27.3% and 31.3% respectively, whilst the risk was 57.6% and 52.8% for A. marginale and B. bigemina, respectively. Major tick species identified include Rhipicephalus appendiculatus, Rhipicephalus decoloratus, Rhipicephalus microplus, Amblyomma variegatum, and Rhipicephalus evertsi. There was great variation (P ≤ 0.001) in the number of all these ticks, both between herds in a state and between calves in an individual herd. The low and intermediate sero-conversion risks observed in the study states suggest that immunisation against East Coast fever (ECF) is justified. Fortunately, three major genotypes that were identified by applying Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCRRFLP) analysis on the p104 to the blood samples and T. parva Muguga, matched very well with T. parva Kiambu 5 and T. parva Muguga; therefore the Muguga cocktail can be used for the immunisation of cattle in South Sudan. However, prospective studies are required to develop optimal control measures for tick-borne diseases under different ecological and husbandry practices in South Sudan.